2020
DOI: 10.1111/andr.12822
|View full text |Cite
|
Sign up to set email alerts
|

Testicular ultrasound score: A new proposal for a scoring system to predict testicular function

Abstract: Background Testicular ultrasound (US) is routinely employed in the evaluation of reproductive and sexual function. However, its use for characteristics other than testicular volume is hampered by a lack of information on the prognostic value of its findings, which to date have only been incorporated in a score proposed by Lenz et al in 1993. Objectives We sought to explore whether testicular US examination can predict the quality of spermatogenesis and provide information on testicular endocrine function. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…In the present study, a mean TV of ~ 17 ml in healthy, fertile men was found. The left TV was smaller than the right one according to some, 6,15,29,46 but not all, 35 the previous studies. In this study, the US‐measured TV lowest reference limit for right and left testis was 12 and 11 ml, respectively.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In the present study, a mean TV of ~ 17 ml in healthy, fertile men was found. The left TV was smaller than the right one according to some, 6,15,29,46 but not all, 35 the previous studies. In this study, the US‐measured TV lowest reference limit for right and left testis was 12 and 11 ml, respectively.…”
Section: Discussionmentioning
confidence: 56%
“…We here report that mean US‐TV in fertile men is positively associated with sperm concentration and total sperm count and negatively with FSH and LH levels. Previous studies reported that US‐estimated TV was positively related to total sperm count, 6,29,42,59,60 sperm motility, 6,42 normal sperm morphology, 6,29 and testosterone levels, 6,32,42 and negatively correlated with LH and FSH 6,42,61 . A negative correlation between US‐TV and non‐conventional sperm parameters (sperm DNA fragmentation, 47,62,63 percentage of spermatozoa with low mitochondrial membrane potential, phosphatidylserine externalization, or chromatin compactness 62,63 ) has been also reported.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…For patients with azoospermia, the chance of a successful pregnancy depends strongly on testicular spermatogenesis function, and biopsy is the reference evaluation criterion (Male infertility Best Practice Policy Committee of the American Urological Association; Practice Committee of the American Society for Reproductive Medicine, 2006). Ultrasound (US) is the cornerstone of primary imaging modalities used for patients with testicular diseases (Lotti & Maggi, 2015; Pozza et al., 2020; Schurich et al., 2009). In addition, sonographic measurements of testicular volume and stiffness have been shown to be associated with male infertility (Du et al., 2010; Huang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%